ANALISIS FILOSOFIS TENTANG PENDIDIKAN ISLAM SEBAGAI SUATU SISTEM DI SDN BUNIASIH KABUPATEN TASIKMALAYA - Warman, Oman; Fachriyah, Neng Vera; Alhaq, Mutia; Nasir, Tatang Muh; Pitriyadi, Sandi Wijaya; Hudah, Iana Rotul (Fakultas Agama Islam Universitas Ibn Khaldun Bogor, 2024)
The style of an educational system appears to be impacted by the viewpoint of each community, group, or nation, according to this article's philosophical examination of Islamic education as a system. This viewpoint has a strong connection to their philosophical upbringing and way of living. Because this way of life indicates an identity that needs to be preserved, developed, and ultimately handed on to the community's younger members. From this viewpoint, it may be inferred that since Islamic education is a system with components, then the Qur'an and Hadith, which serve as the primary Islamic teaching sources, are referenced in the system's design. The fundamental principles of Islamic education, as well as the intended concepts and systems, are typically developed on this basis. The following are some examples of these educational components: educational principles, educational aims, educational materials, educational subjects, and educational objects; educational techniques; educational media; educational evaluation; and educational environment